Transactions on Computational Collective Intelligence XVIII - Nguyen, Ngoc Thanh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
These transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the semantic Web, social networks, and multi-agent systems. TCCI strives to cover new methodological, theoretical and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies, such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This eighteenth issue contains 9 carefully selected and revised contributions.
Using Semantic Web for Generating Questions: Do Different Populations Perceive Questions Differently? -- Reflection of intelligent e-learning/tutoring - the flexible learning model in LMS Blackboard -- GLIO: A New Method for Grouping Like-Minded Users -- A Preferences based Approach for Better Comprehension of User Information Needs -- Performance Evaluation of the Customer Relationship Management Agent s in a Cognitive Integrated Management Support System -- Agreements Technologies - Towards Sophisticated Software Agents in Multi-Agent Environments -- Identification of Underestimated and Overestimated Web Pages Using PageRank and Web Usage Mining Methods -- Massive Classification with Support Vector Machines -- On a Multi-Agent Distributed Asynchronous Intelligence-Sharing and Learning Framework.
Keywords: Artificial intelligence; Engineering; Software engineering; Computer science; Computer simulation; Information systems; Artificial Intelligence; Computational Intelligence; Software Engineering; Computation by Abstract Devices; Simulation and Modeling; Information Systems and Communication Service